UPAYA MENINGKATAN KEMAMPUAN MENGGOLONGKAN BENDA-BENDA YANG BERSIFAT KONDUKTOR DAN ISOLATOR LISTRIK MELALUI PENGGUNAAN METODE EKSPERIMEN PADA SISWA KELAS VI SEMESTER 2 SDN BANDUNGREJO 1 KECAMATAN KARANGANYAR KABUPATEN DEMAK TAHUN PELAJARAN 2013/2014 - Supiyatun . (Universitas PGRI Semarang, 2015)
From the results of preliminary observations made against six graders State Bandungrejo1 Karanganyar District of Demak, the author feels there are still shortcomings in study Natural Sciences with the subject matter to classify objects that are conductors and insulators of electricity. Deficiencies in learning Natural Sciences is because teachers have not been using the method of learning interesting and challenging student activity. This study uses a Class Action Research (PTK). The design of this research action research (Action Research) by using the spiral model. The stages in the implementation of this research is conducted through two cycles. In the classroom action research was used the analysis of quantitative data such as cognitive learning outcomes assessment. This is indicated by the results of the learning improvement obtained average value and completeness increased. The average value before the improvement of learning is then increased to 73.75 67.19 to 81.25 in the first cycle and the second cycle. Percentage of completeness students also increased, where before it was held instructional improvement, the percentage of completeness only 69.00% then increased to 86.00% in the first cycle and 100% in the second cycle. Pengguanaan experimental method can improve students' ability to identify and classify objects that are conductors and insulators of electricity. Keywords: PTK, classify objects conductors and insulators, experimental method